Numerical study of crashworthiness on honeycomb filler subjected to impact loading - Tan, Sze Pei (2019)
Honeycomb filler is known as a good filler for energy absorbing devices in car. Many types of research about honeycomb filler under axial impact had been done and proposed in the literature. However, when it comes to the real situation in an accident, a collision is not only coming from a frontal impact (axial loading). A collision might also come from a different angle (oblique loading). Therefore, crashworthiness in several impact angles are important concern in designing a safe vehicle. The crashworthiness criteria, namely energy absorption (EA) and specific energy absorption (SEA) are related to loading parameters. Safety is the main concern in designing an energy absorber. However, reducing the extra weight caused by the energy absorber is also one of the concerns for manufacturers. This is because the lighter the weight the vehicle has the lesser fuel is consumed to be eco-friendly. In this study, the main objective is to study the performance of honeycomb fillers by different cross-sectional design versus thickness subjected to different angles of impact loading. The investigation is carried out by Finite Element (FE) simulation using ABAQUS software. The investigations of all FE models are carried out by the dynamic impact test. Numerical investigation studies the reaction of three types of honeycomb filler geometric designs which are circular honeycomb filler, hexagon honeycomb filler and multicell. The diameter of every single cell for honeycomb filler is fixed at 10.4 mm. Three different thicknesses of every cell are investigated which are t = 0.06 mm, 0.12 mm, and 0.18 mm. All models are carried out by dynamic impact with both axial and oblique loading which